2021
DOI: 10.18280/ijht.390608
|View full text |Cite
|
Sign up to set email alerts
|

Computational Analysis of Conventional and Helical Finned Shell and Tube Heat Exchanger Using ANSYS-CFD

Abstract: The summary of the proposed work is to compare the rate of heat transfer, logarithmic mean temperature difference (LMTD) and effectiveness (ε) for a conventional shell and tube heat exchanger with and without helical finned surfaces on tube side of heat exchanger. It is shown that the inlet velocity of cold fluid at the tube side varies, while the inlet velocity of hot fluid at the shell side remains constant. The percentage variations of heat transfer rates with theoretical and simulation methods are compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…It was reported that aluminium provides higher heat transfer rates. Several other research highlight the various possibilities of heat transfer [21,22] From the literature, it was understood that a comparison study of analysis between various heat exchangers was not done [23,24]. In the present study, modeling of the heat exchanger was done.…”
Section: Introductionmentioning
confidence: 91%
“…It was reported that aluminium provides higher heat transfer rates. Several other research highlight the various possibilities of heat transfer [21,22] From the literature, it was understood that a comparison study of analysis between various heat exchangers was not done [23,24]. In the present study, modeling of the heat exchanger was done.…”
Section: Introductionmentioning
confidence: 91%
“…Fluid Dynamic Equations. The medium in the fluid domain is incompressible Newtonian fluid in the study, including mass conservation equation and momentum conservation equation, can be expressed as follows [22]:…”
Section: Governing Equationsmentioning
confidence: 99%